2015
DOI: 10.1089/dia.2014.0349
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Variants of Gestational Diabetes in South Indians

Abstract: The rs7754840 and rs7756992 SNPs of the CDKAL1 gene were found to be associated with GDM in this south Indian population. This is the first study describing genetic susceptibility of GDM in Asian Indians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…In addition, there was no significant association between the other two SNPs (rs7754840 and rs1470579) and GDM risk in our study. Consistent with our findings, another study in pregnant Chinese women found no significant association between rs7754840 and GDM risk 18 , whereas studies in Korean, Caucasian and South Indian populations showed significant associations between rs7754840 and GDM risk 12,16,23 . This discrepancy could be due to differences in ethnicities, sample sizes and diagnostic criteria for GDM.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, there was no significant association between the other two SNPs (rs7754840 and rs1470579) and GDM risk in our study. Consistent with our findings, another study in pregnant Chinese women found no significant association between rs7754840 and GDM risk 18 , whereas studies in Korean, Caucasian and South Indian populations showed significant associations between rs7754840 and GDM risk 12,16,23 . This discrepancy could be due to differences in ethnicities, sample sizes and diagnostic criteria for GDM.…”
Section: Discussionsupporting
confidence: 90%
“…DNA was extracted from frozen and stored buffy coats using (QIAGEN Autopure LS kits. Six SNPs previously associated with GDM or T2D in India [ 21 , 22 , 26 , 27 , 30 ] (Additional file 2 : Table S1) and 79 SNPs previously associated with T2D in Europe and elsewhere from GWAS studies up to 2012 (some of these also with GDM risk from candidate gene studies in GDM populations) were genotyped in the present study (Additional file 2 : Table S1) [ 14 ] on a Sequenom Mass ARRAY Platform (Sequenom San Diego, CA, USA) PLEX using MALDI-TOF mass spectrometer [ 31 ] or Taqman allelic discrimination assays using an ABI Prism 7900 sequence detection system (Applied Biosystems, Foster City, CA, USA). Genotyping was performed at the Lund University Diabetes Centre, Sweden after obtaining permission from ICMR (dated 21 october 2010 and Office of Drugs Controller General (India)(dated 14/12/2010).…”
Section: Methodsmentioning
confidence: 99%
“…However, genetic studies of GDM in India are scarce. The SNPs rs7754840 and rs7756992 in the CDKAL1 gene were associated with GDM in South Indian women [ 26 ], while variants in the HMG20A (rs7178572) and HNF4A (rs4812829) genes were associated with both GDM and T2D [ 27 ]. The aim of the present study was to investigate whether a panel of known variants previously associated with GDM and T2D in Indian and European populations are associated with GDM in Punjabi women.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only one Asian GWAS study on GDM in Korean women has been published . Few studies have examined the genetic susceptibility to GDM in the Indian population; these included two studies in South Indian women and reported association of variants in the CDKAL1 , HMG20A and HNF4A genes with GDM . It is quite possible that the genetic background contributing to GDM differs between women of North Indian and women of Scandinavian origin and could explain some disparities in the prevalence of GDM.…”
Section: Introductionmentioning
confidence: 99%